ANALISIS PENERAPAN NILAI KARAKTER DALAM PEMBELAJARAN MATEMATIKA SEKOLAH DASAR: TINJAUAN TERHADAP PEMAHAMAN DAN SIKAP SISWA KELAS IV - Maulina Luthfiana Mustasyfi'ah; Yuli Witanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research seeks to assess how character values are applied within mathematics instruction for fourth-grade elementary students and to explore how these students comprehend and respond to learning that integrates such values. The study took place at SDN Kalibanteng 01 in Semarang City, involving participants from three parallel fourth-grade classes: IVA, IVB, and IVC. A descriptive qualitative method was utilized to carry out the research. Data were obtained through interviews, classroom observations, analysis of documentation, and student questionnaires. Results show that teachers have embedded character values like discipline, honesty, responsibility, collaboration, and religiosity into their mathematics teaching practices. These values were infused both during classroom activities and throughout instructional planning. The incorporation of character values not only enhanced students’ understanding of mathematical concepts but also encouraged more positive, engaged attitudes toward learning. In conclusion, the study emphasizes the vital role of teachers in consistently fostering character values through mathematics education to help nurture well-rounded and morally grounded students.